Analysis of Figurative Language and Imagery in Songs Lyric of Sam Smith’s Album ‘The Lonely Hour’ - Btari Ivena Ithop; Arie Sugiyartati (Tadris Pendidikan Bahasa Inggris IAIN Langsa, 2022)
This research aims to discover the category of words that are taken from an object of speech. The researcher focuses on occurrence frequency and the process of words that have been used in the speech. This research applied a descriptive qualitative method. The researcher collected some words through the speech, and then continued to classify them into morphological analysis, specifically derivational morpheme and inflectional morpheme. The researcher employed the Victoria Fromkin theory to analyze the words and filter them into the derivational morpheme category and inflectional morpheme category. The results reveal the 48 words with 10 of them (21%) represent derivational morphemes. In the derivational morphemes, there are 2 words whose parts of speech do not change and 8 words that do. There are 38 inflectional morphemes (79%) that are divided into 8 categories. These 8 categories consist of 14 plural words, 9 progressive words, 8 past tense words, 2 superlative words, 2 possessive words, 2 third person singular words, and 1 past participle word